2016
DOI: 10.1002/pola.28403
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of fluorinated methacrylate/clay nanocomposite via in‐situ polymerization: Characterization, structure, and properties

Abstract: Novel fluorinated coating containing well-dispersed silicate nanolayers is successfully produced via in-situ free radical polymerization of 2,2,2-trifluoroethyl methacrylate in the presence of vinylbenzyl-functionalized montmorillonite with different loading. The organic modification of sodium montmorillonite is achieved through an ion exchange reaction with triphenylvinylbenzylphosphonium chloride as surfactant prepared before use by reaction with vinylbenyl chloride and phosphine. The following in-situ polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 61 publications
3
16
0
Order By: Relevance
“…With this assumption and the calculated VFT parameters for PMATRIF, T g is determined to be about 80°C. This value is in excellent agreement with the previously measured T g values .…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…With this assumption and the calculated VFT parameters for PMATRIF, T g is determined to be about 80°C. This value is in excellent agreement with the previously measured T g values .…”
Section: Resultssupporting
confidence: 92%
“…This is can be attributed to the creation of a dense polymer package which is the result of the filler loading increase that affect the free volume and hence rise the chain mobility of polymer. A decrease in T g with increasing MMT content has also been reported in previous works of Karamane et al basing on thermal study and was found that the temperature of the vitreous transition of nanocomposites decreased with the incorporation of MMT. This can be explained by the fact that the addition of MMT layers reduces the molecular weight of obtained PMATRIF.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations